Analisis Kecemasan Matematis Siswa SD dengan Menggunakan Neurosains Kognitif (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Mathematics is an important subject so that teachers and parents place certain expectations on students so that students have a good future. However, these expectations can affect the emotional condition of students in learning mathematics so as to allow the occurrence of mathematics anxiety. Mathematical anxiety needs to be considered for its impact and how to overcome it so that researchers want to analyze the impact of math anxiety based on cognitive neuroscience. This research method is descriptive qualitative research using secondary documents in the form of data from questionnaires and interviews with two students who experience math anxiety. Based on the results of the data obtained, it shows that students who experience mathematics anxiety show negative behavior towards mathematics because of hyperactive of the amygdala and experience various difficulties in learning mathematics due to a decrease in the mathematical function of the elementary school students' brain. These data are confirmed by the results of research from various scientists that mathematics anxiety affects the mathematical function of the students' brain. Therefore, teachers need to pay more attention to students who experience mathematics anxiety so that they can follow mathematics lessons well.
Keywords: mathematics; anxiety; student; neuroscience; cognitive